2022
DOI: 10.3390/jcm12010191
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Search Interest for “Suicide” and “Depression” for Particular Days of the Week and Times of Day: Analysis Based on Google Trends

Abstract: Depression is the most common disorder in people who attempt suicide or die by suicide. Research review indicate that therapy of depression (including psychoeducation) is one of the main factors in the prevention of suicidal behavior. In this paper we examine the intensification of search interest for the terms “depression” and “suicide” in Google search engine with regard to the time of day and day of the week in Poland, Germany, Great Britain and Italy. The goal of the study was to determine if there are any… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The authors conducted an extensive analysis of a large number of entries, assessing whether any of them had a direct connection with suicide attempts. In contrast to other cited studies [12,27], which revealed links to suicide attempts with keywords like "depression", "divorce", "unemployment", and complex phrases like "suicide guide", our study explored a broader spectrum of words. For example, a study from Taiwan [28] identified 37 relevant entries featuring the aforementioned terms.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The authors conducted an extensive analysis of a large number of entries, assessing whether any of them had a direct connection with suicide attempts. In contrast to other cited studies [12,27], which revealed links to suicide attempts with keywords like "depression", "divorce", "unemployment", and complex phrases like "suicide guide", our study explored a broader spectrum of words. For example, a study from Taiwan [28] identified 37 relevant entries featuring the aforementioned terms.…”
Section: Discussionmentioning
confidence: 98%
“…Google Trends has been used in many different infodemiology studies for analysis [8,[12][13][14][15]. It has also revealed correlations between the frequency of certain search phrases and mental health conditions and addiction rates [12]. Researchers have made attempts to correlate specific search phrases with fluctuations in suicide rates [12,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Google Trends has the ability to examine the window of time during which search terms are most frequent. Literature show that searches for "suicide" and "depression" usually occures on weekends, especially late at night [51] . Such information indicates the necessity of providing psychological assistance calls during weekends and late-night hours.…”
Section: Mental Healthmentioning
confidence: 99%